Academy Literacy - Pugh, Sharon L. (Journal of Modern Languages, 2017)
This paper looks at academic literacy in terms of micrological and macrological perspectives. The study considers the notions of critical thinking movement, and frameworks for relating language processes in relation to literacy as well.